2021
DOI: 10.1007/s12022-021-09675-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Paragangliomas and Pheochromocytomas: from Histology to Molecular Immunohistochemistry

Abstract: Abdominal paragangliomas and pheochromocytomas (PPGLs) are rare neuroendocrine tumors of the infradiaphragmatic paraganglia and adrenal medulla, respectively. Although few pathologists outside of endocrine tertiary centers will ever diagnose such a lesion, the tumors are well known through the medical community—possible due to a combination of the sheer rarity, their often-spectacular presentation due to excess catecholamine secretion as well as their unrivaled coupling to constitutional susceptibility gene mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 117 publications
0
46
0
Order By: Relevance
“…Though both genes are highly associated with PCCs and PGLs, the pathogenicity of these variants remains uncertain in this case. However, it has been reported that SDHB, C, or D mutated cases display SDHB immunonegativity [ 23 , 24 ], and the SDHB immunostaining in PGL of this case was positive, so it has been suggested that the pathogenicity of the SDHD variant in this case is low. Meanwhile, 28 gene mutations, including 8 germline mutations, have been reported in follicular lymphoma [ 25 ], but no candidate mutations were detected among those genes.…”
Section: Discussionmentioning
confidence: 77%
“…Though both genes are highly associated with PCCs and PGLs, the pathogenicity of these variants remains uncertain in this case. However, it has been reported that SDHB, C, or D mutated cases display SDHB immunonegativity [ 23 , 24 ], and the SDHB immunostaining in PGL of this case was positive, so it has been suggested that the pathogenicity of the SDHD variant in this case is low. Meanwhile, 28 gene mutations, including 8 germline mutations, have been reported in follicular lymphoma [ 25 ], but no candidate mutations were detected among those genes.…”
Section: Discussionmentioning
confidence: 77%
“…Tumor cells exhibit a granular and slightly basophilic cytoplasm, and nuclei can vary in size and appearance, with either mono- or pleomorphic features [ 13 , 73 ]. Immunoreactivity to classic neuroendocrine markers such as CgA and synaptophysin is almost always present, and second-generation neuroendocrine markers ISL LIM Homeobox 1 (ISL1) and INSM1 have also been found as reliable markers of an adrenal medullary origin in pheochromocytoma [ 74 , 75 , 76 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies are playing a growing role in the clinical investigation and management of various cancers in the developed world. This is true for endocrine neoplasias like PPGL, where a large number of new target genes have been identified recently (17). In the developing world, technological and budgetary constraints conspire to limit greatly the availability and use of clinical genetics, thereby hindering optimal management.…”
Section: Discussionmentioning
confidence: 99%